Results of cement spacer sonication in the second stage of two-stage treatment of shoulder arthroplasty infection - Torrens, Carlos (J Orthop Surg Res, 2018)
BACKGROUND: The objective of this study is to present the results of cement spacer sonication in the second stage of two-stage treatment of shoulder arthroplasty infection and to determine the rate of positive cultures in the second-stage surgery in shoulder arthroplasty and its meaning. METHODS: Twenty-one patients (22 cement spacers) treated with two-stage surgery because of a shoulder arthroplasty infection were included. In the second stage, the cement spacer was sent for sonication and at least four tissue cultures were obtained. Epidemiological data, comorbidities, sensitivity of the microorganisms to the antibiotic loaded in the cement spacer in the first revision surgery, time elapsed since an antibiotic was last administered until second revision procedure, functional shoulder status at last follow-up, and any complication were recorded. RESULTS: Three out of the 22 cases (13.6%) presented positive cultures at the second-stage surgery. Periprosthetic tissue culturing detected the three positive culture cases in the second stage while the cement spacer sonication detected two and missed one. Considering periprosthetic tissue culturing as the standard procedure, the cement spacer sonication showed sensitivity at 66.6%. Recurrent infection over time was considered present in 3 patients; two of them had been previously diagnosed with a positive culture at the second stage (66.6%). CONCLUSIONS: A good number of patients (13.6%) present a positive culture at the second stage of the two-stage surgical procedure for infected shoulder arthroplasty, and those patients seem to be at high risk for recurrent infection. Periprosthetic tissue cultures have a higher sensitivity to detecting a positive culture at the second stage than cement spacer sonication.